Characteristics of stress and plastic zone of a deep shaft in a nonuniform stress field considering the bearing structure. Issue 5 (October 2020) - Sun, X M; Zhao, C W; Zhang, Y; Cui, L; Wang, J; Zhang, S K; Shen, Z H
Abstract: The selection of support parameters for the shaft of a deep soft rock under a nonuniform stress field (NSF) is a technical challenge. In this study, the distribution characteristics of the maximum stress-bearing circle were investigated via a numerical simulation. Based on the characteristics of the shaft rock-bearing structure, the stress and plastic zone characteristics of deep shaft rock under NSF were investigated. The maximum stress-bearing circle expanded with depth and NSF coefficient under the no-support scheme, and the stress-bearing circle was circular when the NSF coefficient was 1. When the NSF coefficient was greater than 1, the stress-bearing circle began to show an elliptical nonuniform distribution characteristic along the long axis in the y-axis. As the NSF coefficient and depth further increased, the elliptical effect became more obvious. A constant resistance and large deformation (CRLD) cable was used to control the stability of the shaft under NSF. The stress-bearing circle and plastic zone under the CRLD cable-support scheme were smaller than those under the no-support scheme. Furthermore, the peak stress under the CRLD cable-support scheme was higher than that under the no-support scheme, which indicated that CRLD cable support could improve the bearing capability of the surrounding rock and reduce the plastic zone caused by the NSF coefficient. The findings of this study can provide reference for the supporting parameters for deep shafts.